Interaction of curcumin in a drug delivery system including a composite with poly(lactic-co-glycolic acid) and montmorillonite: a density functional theory and molecular dynamics study - Karatas, D.; Tekin, Adem; Bahadori, FATEMEH; BAHADORİ, FATEMEH; Çelik, Mehmet Sabri (My University, 2017)
Phytochemicals such as curcumin have great potential in cancer prevention and treatment. However, instability and low aqueous solubility of free curcumin weaken its anticancer potential. These undesirable problems can be avoided upon loading curcumin into nanoparticles containing biocompatible and biodegradable polymers such as poly lactic-co-glycolic acid (PLGA), liposomes or micelles. The interaction of drugs and release control can be further enhanced upon inclusion of clay minerals into the PLGA containing nanoparticles. Such nanoparticles offer a new way for cancer drug delivery systems. However, the role of the clay mineral in the resulting composite is not fully understood. Therefore, in this study, we carried out systematic adsorption studies of curcumin anticancer drug on montmorillonite (MMT) nanoparticles in the presence of amphiphilic polymer (PLGA) and in an aqueous environment to understand the contribution of the layered clay structure using cluster (B97-D), periodic DFT and molecular dynamics (MD) simulations in acidic and natural pH media. It has been found that MMT has high affinity towards either polymer or drug molecules especially due to vdW interactions. Furthermore, it has been observed that MMT facilitates the release of curcumin. Current findings suggest that a composite consisting of MMT and PLGA might be used to deliver the anticancer agent curcumin.